Analysis of Intersectional Hybrids of Dendrobium by RAPD Technique - Sirilak Inthawong; Weenun Bundithya; Nuttha Kuanprasert; Pimchai Apavatjrut (Agriculture and Natural Resources, 2006)
Thirty interspecific hybridizations of inter- or intra-section of Dendrobium were made. Five crosses showed good compatibility and could yield hybrids as follows: 2 intersectional hybridizations, 1) section Phalaenanthe: Den. phalaenopsis (D017) × section Formosae: Den. draconis (D022) and 2) section Dendrobium: Den. finlayanum (D030) × section Formosae: Den. cariniferum (D018); and 3 intrasectional hybridizations, 1) section Dendrobium: D030 × Den. nobile (D031), 2) section Formosae: Den. trigonopus (D037) × D022, and 3) D037 × Den. infundibulum (D034). The greatest number of plantlets (1,250 plantlets) was obtained from cross D037 × D022 whereas the least number (3 plantlets) was found in cross D037 × D034. After transplanting for 6 months, survival rate of D037 × D034 was 100% whereas no survival plant was found in cross D030 × D018. Parents and hybrids of 5 crosses were analyzed by RAPD using 21 decamer primers and the number of primers generating polymorphic patterns of each cross varied. RAPD markers were able to differentiate parents in inter- and intra-sectional crosses and these markers could confirm the interspecific hybrids.